Core and Valence Structures in KβX‑ray Emission Spectra of Chromium Materials - Torres Deluigi, María del Rosario (2014)
We analyze the core and valence transitions in chromium in a series of materials with a number of different ligands and including the oxidation states: CrII, CrIII, CrIV, and CrVI. To study the core-to-core transitions we employ the CTM4XAS program and investigate the shapes, widths, intensities, and energy positions of the Kβ1,3 and Kβ′ lines in each oxidation state. The theoretical spectra are compared with experimental data obtained with synchrotron radiation. We found that the Kβ1,3 peak shifts to higher energy with increasing spin state. In addition, the widths of the Kβ1,3 peak increases as the oxidation state decreases, which we explain from the increased spread of the multiplet structures. In the Kβ′ structure the presence of two peaks in CrII, CrIII, and CrIV is due to the large 3p3d exchange interaction. For the analysis of the valence transitions we utilize the DV-Xα method. We study the dependence of the relative intensities of the Kβ″ and Kβ2,5 structures on symmetry, bond length, and the effective number of 3d and 4p electrons in different chemical environments